Disability in perioperative activities of daily living is associated with worse survival outcomes following hepatic resection in patients with intrahepatic cholangiocarcinoma. Issue 2 (14th November 2022) - Mima, Kosuke; Hayashi, Hiromitsu; Yumoto, Shinsei; Matsumoto, Takashi; Tsukamoto, Masayo; Miyata, Tatsunori; Nakagawa, Shigeki; Nitta, Hidetoshi; Baba, Hideo
Abstract: Aim: Intrahepatic cholangiocarcinoma (ICC) is a rare disease; however, its incidence and mortality are increasing worldwide. The rapid aging of populations around the world is leading to an increased number of patients with cancer who develop disability in activities of daily living (ADL). This study was conducted to investigate the associations of perioperative ADL with patient survival after hepatic resection for ICC. Methods: We included 70 consecutive patients who underwent hepatectomy for ICC from 2010 to 2021 in the current study. Preoperative and postoperative ADL were evaluated based on the Barthel index, which yields a score of 0–100 points, with higher scores indicating greater independence. A preoperative or postoperative Barthel index score of <100 was defined as disability in perioperative ADL. Cox proportional hazards regression was used to calculate hazard ratios after adjusting for potential confounders. Results: Among the 70 patients, seven (10%) had a preoperative Barthel index score of <100, and 23 (33%) showed a postoperative Barthel index score of <100. Multivariate analyses revealed that disability in perioperative ADL was associated with shorter recurrence‐free survival (multivariable hazard ratios 2.38, 95% confidence interval 1.22–4.57; p  = 0.011) and overall survival (multivariable hazard ratio 2.49, 95% confidence interval 1.09–5.70; p  = 0.031). Conclusions: Disability in perioperative ADL is associated with shorter recurrence‐free and overall survival after hepatic resection for ICC. Upon validation, perioperative measurement of ADL may improve risk assessment, and improvement of perioperative ADL may lead to favorable clinical outcomes in patients with ICC. Abstract : Integration of perioperative Barthel index scores into clinical practice may improve risk assessment in patients with ICC, and improving preoperative disability and preventing a decline in ADL following hepatic resection may lead to favorable clinical outcomes, particularly in older or vulnerable patients with ICC.